The uses and gratifications of multimedia integration in Malaysian online news consumption - Ng Wei Liang; Lee Kuok Tiung (RSIS International, 2025)
Focusing on the online news consumption scenario in Malaysia, this paper uses the "Uses and Gratifications Theory" (U&G) as a theoretical lens to deeply deconstruct the behavior of multimedia integration in online news. Through a quantitative questionnaire survey of 328 (N=328) Malaysian audiences. This paper deeply analyses the user needs, usage pattern and gratification of multimedia elements such as video, infographics, interactive functions and social media integration in news portals. The findings found that audience needs present a clear hierarchical structure: cognitive needs is dominant, and audiences have a significant preference for multiple media forms that can effectively simplify complex information. At the uses level, Malaysian audiences are highly dependent on multimedia for information seeking, but their information sharing behavior is significantly limited, reflecting the unique local cultural characteristics. Gratification analysis reveals a "form-function paradox", compared with pure -text presentation, video content can bring higher gratification; and social gratification strongly confirms the role of multimedia news as a tool for strengthening social interaction. In addition, technology needs and gratification present a subtle duality: on the one hand, users have a positive overall experience evaluation, and on the other hand, they are critical of the design of specific interactive functions. Correlation analysis further verifies the significant correlation between user needs, media use behavior and gratifications dimensions, thereby strengthening the empirical validity of the multidimensional framework. By explaining the multimedia-integration news consumption and constructing a cognitive-social dual-core model, this study significantly promotes the research progress of multimedia journalism and provides practical suggestions for optimizing news portal strategies.